Predictive study of fluid flow through an intake system restrictor of a single-seater racing car - Zaqout, Ahmed Z. I. (2018)
The society of Automotive Engineers conducts an annual student design competition referred to as Formula SAE (FSAE).Teams are limited to a 610 cc engine that is restricted by a 20 mm air restrictor.The restrictor limits the power output by reducing mass flow rate flowing to the engine.Thus,the aim of this project is to design and predict the flow behaviour of a flow restriction device to be installed in the single seater race car.The design consists of a converging part (nozzle) and a diverging part (diffuser) with the 20mm throat mandated by the FSAE rules being in the middle.The nozzle design was based on the work of T.Morel on axisymmetric wind tunnel contractions as a way to explore different aspects of the restrictor geometry criterion. While the diffuser geometry was obtained from previous optimizations.The simulation was carried out with the academic version of Ansys 17.2 Workbench which was conducted in 2D-axisymmetric geometry with isothermal process.Nozzle design comparison between contraction ratios of 16 and 9 were performed.The simulation applied the local mesh with appropriate controls in order to obtain correct predictions of the flow behaviour near the walls.Velocity and pressure contours,velocity vectors and surface monitors showed that the novel design with contraction ratio 16 displays superior pressure recovery characteristics than that of contraction ratio 9 with pressure difference of 12610 Pa and 15758 Pa respectively.However,there is always more room for improvements considering the design is in the development stage.Furthermore,based on the design criterion of the restrictor,separations are avoided completely for both designs.